Pelatihan dan Pengembangan Perangkat Pembelajaran Berdasarkan Permendikbud Nomor 22 Tahun 2016 pada Guru-Guru di Gugus V Kediri, Kecamatan Kediri Kabupaten - Sudana, Dewa Nyoman (Universitas Pendidikan Ganesha, 2018)
This activity was a community work in education. The purpose of this activity was to improve elementary school teachers’ ability in SD Gugus V of Kediri district of Tabanan regency in developing teaching materials based on the Regulation of the Minister of Education and Culture No. 22 of Year 2010. This community work was done in seven months starting from 2nd April, 2017 by giving knowledge about materials development in the form of training and tutoring using lecturing, question and answer, discussion and assignment methods. To know the teachers’ ability in writing lesson plans, observation and task assessment methods were used. The results of obserrvation showed that all of the 25 participating teachers were enthusiastic from the beginning to the end of the activity. While from the assessment of the tasks in the form of materials development it was shown that 96% or 24 teachers understood and were able to write lesson plans well and 4% or 1 person had a good ability. From the results obtained it can be stated that the implementation of P2M in Gugus V, Kediri district, Tabanan regency was done smoothly and successful.